Comparative study, homology modelling and molecular docking with cancer associated glycans of two non-fetuin-binding Tepary bean lectins - Iovanna Torres-Arteaga; Alejandro Blanco-Labra; Elizabeth Mendiola-Olaya; Teresa García-Gasca; Cesar Aguirre-Mancilla; Alondra L. Ortega-de-Santiago; Mariana Barboza; Carlito B. Lebrilla; José Luis Castro-Guillén (Glycoconjugate Journal, 2023)

Agrobacterium rhizogenes-mediated transformation of grain (Amaranthus hypochondriacus) and leafy (A. hybridus) amaranths - Andrea P. Castellanos-Arévalo; Andrés A. Estrada-Luna; José L. Cabrera-Ponce; Eliana Valencia-Lozano; Humberto Herrera-Ubaldo; Stefan de Folter; Alejandro Blanco-Labra; John P. Délano-Frier (Plant Cell Reports, 2020)

Exclusive rewards in mutualisms: ant proteases and plant protease inhibitors create a lock–key system to protect A cacia food bodies from exploitation - Domancar Orona‐Tamayo; Natalie Wielsch; Alejandro Blanco‐Labra; Ales Svatos; Rodolfo Farías‐Rodríguez; Martin Heil (Molecular Ecology, 2013)
Myrmecophytic A cacia species produce food bodies ( FB s) to nourish ants of the P seudomyrmex ferrugineus group, with which they live in an obligate mutualism. We investigated how the FB s are protected from exploiting nonmutualists. Two‐dimensional gel electrophoresis of the FB proteomes and consecutive protein sequencing indicated the presence of several Kunitz‐type protease inhibitors ( PI s). PI s extracted from A cacia FB s were biologically active, as they effectively reduced the trypsin‐like and elastase‐like proteolytic activity in the guts of seed‐feeding beetles ( P rostephanus truncatus and Z abrotes subfasciatus ), which were used as nonadapted herbivores representing potential exploiters. By contrast, the legitimate mutualistic consumers maintained high proteolytic activity dominated by chymotrypsin 1, which was insensitive to the FB PI s. Larvae of an exploiter ant ( P seudomyrmex gracilis ) taken from A cacia hosts exhibited lower overall proteolytic activity than the mutualists. The proteases of this exploiter exhibited mainly elastase‐like and to a lower degree chymotrypsin 1‐like activity. We conclude that the mutualist ants possess specifically those proteases that are least sensitive to the PI s in their specific food source, whereas the congeneric exploiter ant appears partly, but not completely, adapted to consume A cacia FB s. By contrast, any consumption of the FB s by nonadapted exploiters would effectively inhibit their digestive capacities. We suggest that the term ‘exclusive rewards’ can be used to describe situations similar to the one that has evolved in myrmecophytic A cacia species, which reward mutualists with FB s but safeguard the reward from exploitation by generalists by making the FB s difficult for the nonadapted consumer to use.

Trypsin inhibitors in xoconostle seeds (Opuntia joconostle Weber.) - María Teresa Aguirrezabala-Cámpano; Reyna Ivonne Torres-Acosta; Alejandro Blanco-Labra; Ma. Elizabeth Mediola-Olaya; Sugey Ramona Sinagawa-García; Adriana Gutiérrez-Díez; Jorge Ariel Torres-Castillo (Journal of Plant Biochemistry and Biotechnology, 2013)

Cloning and characterization of a trypsin inhibitor cDNA from amaranth (Amaranthus hypochondriacus) seeds - Silvia Valdés-Rodríguez; Alejandro Blanco-Labra; Glenda Gutiérrez-Benicio; Anatoli Boradenenko; Alfredo Herrera-Estrella; June Simpson (Plant Molecular Biology, 1999)